Testing a model of UK growth: A role for R&D subsidies - Lucy Barros (Economic Modelling, 2019)
Debate continues on the economic growth effects of direct support for business R&D. We set out aDSGE model of the UK in which direct R&D subsidies drive total factor productivity (TFP) throughtheir incentive effects on agents' optimal decisions. We estimate and test the model by IndirectInference, finding that this model can account for the joint behaviour of UK output and TFP. The model allows us to analyse the short-run impact of R&D subsidies on TFP and to quantify the longer-term impacts of R&D subsidy shocks on output. We also determine uncertainty bounds for key growth parameters using Monte Carlo analysis. Our results show that even temporary policy cuts to R&D funding have long-lasting impacts on UK economic growth. The findings are of great policy relevance given ongoing debate around the future UK innovation environment and the novel application of indirect inference to this question.